Rekonstruksi Hambatan Psikologis Mahasiswa melalui Integrasi Coping Adaptif dan Spiritual dalam Pendidikan Islam - Asrofik; Ahmad Said; Ahmad Naweed Rahimi Khamosh (STAI Ma'had Aly Al-Hikam Malang, 2025)
This conceptual study reconstructs psychological barriers among university students as a dynamic interaction between educational demands, personal appraisal, internal vulnerability, and external pressure. The discussion moves beyond a symptom-based view that treats stress, anxiety, withdrawal, and academic delay as isolated personal weaknesses. It proposes an integrative framework that combines transactional coping theory, biopsychosocial analysis, Islamic spiritual coping, and an educational ecosystem perspective. The study employs qualitative library research with analytical, comparative, and conceptual synthesis of psychological, educational, and Islamic studies literature. The analysis shows that psychological barriers emerge when demands are perceived as exceeding available cognitive, emotional, social, material, and spiritual resources. Adaptive coping becomes effective when it matches the controllability of the stressor, while spiritual practices contribute through meaning, hope, emotional regulation, and ethical orientation. However, spiritual coping should not replace professional assistance when symptoms cause persistent functional impairment. The article develops an integrative model consisting of early recognition, appraisal correction, adaptive coping, spiritual meaning-making, social support, and institutional referral. Its novelty lies in positioning Islamic spiritual coping as a complementary mechanism within a layered educational support system rather than as a single solution. The model offers a conceptual basis for mental-health literacy, counselling services, and responsive pedagogy in Islamic higher education.